Climate change research on transportation systems: Climate risks, adaptation and planning. (November 2020) - Wang, Tianni; Qu, Zhuohua; Yang, Zaili; Nichol, Timothy; Clarke, Geoff; Ge, Ying-En
Highlights: Conduct critical analysis on climate adaptation study in transportation. Introduce a new classification method with reference to diverse key topics. Identify the research gaps through statistical and qualitative analysis. Guide future research directions in transport adaptation to climate change. Abstract: With the occurrence of more frequent and intense climate change events, transportation systems, including their infrastructure and operations become increasingly vulnerable. However, the existing research related to climate risks, adaptation and planning in the transport sector is still at an embryonic stage. Understanding such, this paper presents a critical review on climate risks, adaptation strategies and planning in the context of road and rail transportation systems. It aims to conduct a rigorous survey, to highlight any significant research gaps not addressed in past studies and to analyse current emerging topics to guide future directions. It critically dissects the selected papers by categorising them into several dimensions to reveal the status quo and potential challenges, including climate risk assessment, transport asset management, climate planning and policy, and adaptation of transport infrastructure to climate change. It will provide valuable references for future research and constructive insights and empirical guidance on climate adaptation, risk analysis, transport planning and other important relevant topics.